ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ ТРАНСПАРЕНТНОСТІ ПРОКУРАТУРИ - Банах, Сергій (SUPREMANCE OF LAW, 2018)
The general provisions of information support of the prosecutor’s offices of Ukraine as an element of transparency in the modern rule of law are studied. The peculiarities of information in prosecutorial activity and its influence on the formation of openness of law enforcement agencies in general and the prosecutor’s office in particular are analyzed. The legal bases for ensuring the transparency of the prosecutor’s office and the expediency of delineating its legal boundaries are considered. The position that the legal activity of the prosecutor when working with information is an indicator of the standard of legality of the prosecutor’s office is substantiated.